Answer:
(f•g)(2)=3 and (g•f)(6)=7
Step-by-step explanation:
look at the tables
where x is equal to both 2 and 7 is where you will find your answer
Hope this helps you!
A=
B=
C=
Answer:
A = 3
B = -7
C = -12
Step-by-step explanation:
3x^2−7x=12.
The standard form for a quadratic equation is
Ax^2 +Bx +C =0
Subtract 12 from each side
3x^2−7x-12=12-12
3x^2−7x-12=0
A = 3
B = -7
C = -12
Answer:
a = 3
b = -7
c = -12
Step-by-step explanation:
General form of a quadratic:
ax² + bx + c
Given:
3x² − 7x = 12
3x² - 7x - 12 = 0
Comparing the two:
a = 3
b = -7
c = -12
C.2
D.3 1/2
the correct answer is C
make the mixed number to an improper fraction:
7/2 × 4/7
cross simplify and you get 1/1 × 2/1
so your final answer is: 2
Answer:
Step-by-step explanation:
Do